2021
DOI: 10.1093/ecco-jcc/jjab023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety and Efficacy of the Anti-MAdCAM-1 Monoclonal Antibody Ontamalimab [SHP647] for the Treatment of Ulcerative Colitis: The Open-label Study TURANDOT II

Abstract: Background and Aims Ontamalimab, a fully-human monoclonal antibody targeting MAdCAM1, induced remission in patients with moderate-to-severe ulcerative colitis (UC) in TURANDOT. We assessed long-term safety, tolerability and efficacy of ontamalimab in TURANDOT II. Methods TURANDOT II was a phase 2, multicentre, open-label (OL) study in patients with moderate-to-severe UC who completed TURANDOT on placebo or ontamalimab. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…There were no significant differences between ontamalimab and placebo in adverse events, no dose‐related increase in adverse effects and no serious infections or PML 44 . In the OLE, patients were randomised to receive ontamalimab 75 or 225 mg every 4 weeks for 72 weeks 45 . In this group, 36.1% had drug‐related AEs, the most common being worsening UC (10.0% and serious infection (5.5%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no significant differences between ontamalimab and placebo in adverse events, no dose‐related increase in adverse effects and no serious infections or PML 44 . In the OLE, patients were randomised to receive ontamalimab 75 or 225 mg every 4 weeks for 72 weeks 45 . In this group, 36.1% had drug‐related AEs, the most common being worsening UC (10.0% and serious infection (5.5%).…”
Section: Resultsmentioning
confidence: 99%
“…There were 1 death and 4 cancers, but all were deemed unrelated to the study drug. Patients who initially received placebo and then received study drug in the OLE had mucosal healing rates increase from 8.8% at baseline to 35.3% at week 16 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who completed the 12 weeks of treatment were subsequently included in the ongoing, 144-week open-label extension trial TURANDOT II to assess the long-term safety of PF-00547659. Conversely, PF-00547659 failed to demonstrate efficacy in CD [ 107 ]. The OPERA trial, a randomized, double-blind, placebo-controlled phase II study, included moderate to severe CD patients (CDAI range: 220–450) who failed immunosuppressive drugs or anti-TNF-α [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…An open-label dose escalation extension of the TURANDOT trial demonstrated acceptable drug tolerance, with 36.1% of patients experiencing drug-related adverse events (AEs), with the most common serious AE being worsening or ongoing UC, followed by serious infection. 80 Ontamalimab was originally developed by Pfizer, which licensed it out to Shire back in 2016. Takeda later acquired Shire in 2019.…”
Section: Ontamalimab (Pf-00547659 or Shp647)mentioning
confidence: 99%